Quantification of anterior translation of tibia over femur using Lachmeter in anterior cruciate ligament reconstruction with hamstring tendon autograft - K. D., Vishnu; Samuel E., Samson; John, P. S. (International Journal of Research in Orthopaedics, 2024)
Background: The anterior cruciate ligament (ACL) is an important restraint on anterior tibial translation of the knee. Arthroscopic ACL reconstruction using hamstring tendon autograft is the most widely accepted surgical procedure for ACL insufficiency. This study is assessing the effect of ACL reconstruction by hamstring tendon autograft on the anteroposterior stability of the knee joint by measuring the side-to-side difference of anterior tibial translation using the Lachmeter. We are also assessing the functional outcome of the same surgery using international knee documentation committee (IKDC) score. Methods: The study included 30 patients who were admitted for ACL reconstruction with hamstring tendon autograft. The side-to-side difference of anterior tibial translation was assessed by using Lachmeter preoperatively and postoperatively at the end of the 1st, 3rd, and 6th months. The IKDC score was assessed preoperatively and postoperatively at the end of 6th month. Results: The mean Lachmeter value of respondents in the current study was 4.31±0.56 mm during the preoperative period. Lachmeter values were 2.79±0.42 mm, 2.09±0.42 mm, and 1.29±0.39 mm, respectively, at the end of the first, third, and sixth months postoperatively. Mean preoperative and postoperative 6th month IKDC scores were 55.83±7.7 and 89.20±5.3 respectively. Conclusions: There is significant serial improvement in the side-to-side difference of anterior tibial translation in the 6 months of post operative period following ACL reconstruction using hamstring tendon autograft. The improved IKDC score from preoperative to postoperative level is also indicating a positive functional outcome.